VD_FINDINFO Jug / 2020 / 1 vom 3. April 2020 - VD Tribunal cantonal (2020)
LÉGITIMATION ACTIVE ET PASSIVE, RESPONSABILITÉ CONTRACTUELLE, LIEN DE CAUSALITÉ, DOMMAGE | 394 CO, 42 CO, 46 CO, 47 CO, 61 CO